Acute increases in brain-derived neurotrophic factor following high or moderate-intensity exercise is accompanied with better cognition performance in obese adults - Inoue, Daniela Sayuri [UNESP]; Monteiro, Paula Alves [UNESP]; Gerosa-Neto, José [UNESP]; Santana, Priscilla Rodrigues; Peres, Fernando Pierin; Edwards, Kate M.; Lira, Fabio Santos [UNESP] (Springer Nature, 2020)
The purpose of this study was to test if different intensities of aerobic exercise could influence abdominal fat, isoforms of BDNF and executive function. Twenty obese men (30.0 ± 5.4 years old; 34.4 ± 3.5 kg/m2) were randomized to moderate-intensity continuous training (MICT, n = 10) and high-intensity intermittent training (HIIT, n = 10) three times a week for 6 weeks, with isoenergetic energetic expenditure for each exercise session (~ 300 kcal) between conditions. Abdominal fat was assessed pre- and post-intervention; executive function (Coding subtest from BETA-III non-verbal intelligence test and Stroop Color and Word Test), concentrations of mBDNF and proBDNF were assessed in response to acute exercise pre- and post-intervention. Abdominal fat did not change in either group. There was a significant increase in mBDNF immediately after acute exercise in both groups before and after intervention. proBDNF did not present changes acutely nor after 6 weeks. Executive function presented a main effect of time at pre- and post-intervention time-points Stroop Word and Stroop Color and Coding subtest presented improved performance from pre- to post-acute exercise session, in both groups. In conclusion, executive function improvements and acute exercise session-induced increases in mBDNF concentration were found from pre- to post-exercise intervention similarly between MICT and HIIT in obese men.